Indian Woman and Child, Trinidad - (:unkn) unknown (Thomas' Studio, Port of Spain, Trinidad and Tobago [Printed in Saxony], 2008)
Photograph of an East Indian woman holding a baby.
Colour: Brown, black and white; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; Children--Trinidad and Tobago; Trinidad and Tobago; East Indians--Trinidad and Tobago; Ethnic costume--India; Bracelets--India; Clothing and dress--Trinidad and Tobago; Women's clothing--Trinidad and Tobago